Big Boys Don't Cry: A Critical Interpretive Synthesis of Male Sexual Victimization. (December 2020) - Depraetere, Joke; Vandeviver, Christophe; Beken, Tom Vander; Keygnaert, Ines
Sexual victimization is typically presented as a gender-based problem involving a female victim and a male offender. Science, policy, and society focus on female victims at the expense of male victims. Male sexual victimization is thus understudied compared with female sexual victimization. By performing a critical interpretive synthesis of research papers, policy documents, and gray literature ( N = 67) published in four electronic databases from January 2000 through September 2017, this article establishes the prevalence of male sexual victims and the causes that underlie the underrepresentation of this group in existing research and current policy. The prevalence rates of male sexual victims vary considerably, with up to 65% of men reporting sexual victimization. The underrepresentation of male victims was found to be rooted in prevailing gender roles and accepted sexual scripts in society, together with rape myths and stereotypical rape scripts. The former prescribes men as the dominant and sexually active gender. The latter denies male sexual victimization and frames women as "ideal victims." Combined, these prevailing societal perceptions of men, male sexuality, and sexual victimization prevent men from self-identifying as victims and inhibit them from seeking help to cope with the adverse consequences of sexual victimization. Addressing the gender differences in sexual victimization requires societal and political changes that challenge prevailing stereotypical perceptions of sexual victims. Such changes could result in improved support services for male sexual victims.